Engineering Student Experiences of Group Work - Amin Reza Rajabzadeh; Jennifer Long; Guneet Saini; Melec Zeadin (MDPI AG, 2022)
Soft skills are a crucial component for success in today's workplace as employers increasingly value work that is collaborative and encompasses diverse perspectives. Despite this, most engineering programs fail to explicitly teach students transferable skills, including the best practices of group work. This research sought to explore how undergraduate experiences of group work change over time. This research also investigated what reflecting on cooperative education (co-op) experiences tells us about teaching group work in academic settings. Despite frequently noting the influence of group work in developing their communication skills and brainstorming ideas over time, students become somewhat more frustrated over time with their experiences of group work, mainly due to conflicting personalities and ideas among team members and/or a "slacker" student. However, our findings also show that students become more confident working in teams over time, as upper-year students were more likely to assume a leadership role and self-reported higher past performance as a group member. This study offers insights into the changing group work experiences of undergraduate engineering students as they progress through coursework and engage in experiential learning and work-integrated learning opportunities, such as co-op placements. The findings of this study can inform educators on how to best incorporate methods for teaching transferable soft skills.